Comparison of Hemodynamic Changes Associated with Two Different Concentrations of Adrenaline in 2% Lignocaine Solution (International Journal of Food and Nutritional Sciences, 2022)
Local anesthetic (LA) drugs are frequently used to manage pain during surgical procedures in dentistry. Different amounts of adrenaline have been added to a range of LA agents on the market to boost their effectiveness. Although the systemic effects of adrenaline, which is utilized as a vasoconstrictor in LA solution, are momentary or fleeting, there have been cases of related cardiovascular issues. This study compares the cardiovascular effects and effectiveness of using two different doses of adrenaline with 2% lignocaine.